Reinventing talent management: How to maximize performance in higher education - Ramaditya, Muhammad; Maarif, Mohamad Syamsul; Affandi, Joko; Sukmawati, Anggraini (Frontiers in Education, 2022)
To survive in the ever-competitive world, higher education institutions must implement various sustainable strategies. For instance, the concept of talent management has attracted attention in academic institutions, especially universities. The purpose of this study was to explain how talent management, knowledge management, university transformation, and academic climate can shape talents and contribute to improved higher performance in education. A quantitative approach was utilized to obtain 382 primary data from questionnaires distributed to lecturers drawn from different private universities in Indonesia. Furthermore, the data were analyzed using SmartPLS software. The findings indicated that systematic application of talent and knowledge management, university transformation, and academic climate in higher education supports improved performance. The study contributes to the theoretical and empirical discussion by addressing increasing change and uncertainty. As a result, insight is given to shape talent and other managerial perspectives in maximizing performance.